ANALISIS MINAT PENGGUNAAN APLIKASI FORECASTING SATKER DALAM RANGKA PERENCANAAN KAS (Studi Kasus pada Satuan Kerja Wilayah Pembayaran KPPN Jakarta IV) - Komang Ayu Kumaradewi; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2013)
This research identifies the factors that influence users’ intention to use Work-unitsForecasting Application (Aplikasi Forecasting Satker – AFS) as a manifest of e-governmentimplementation, especially in performing cash management issue. The theoretical model in thisresearch based on the Technology Acceptance Model (TAM).A total of 410 (four hundred and ten) questionnaires were distributed, 128 (a hundred andtwenty eight) questionnaires were returned and 121 (a hundred and twenty one) quesionnaireswere found usable. The data were subjected to Structural Equation Modelling (SEM) analysisusing SmartPLS.Results indicate that the important determinants of users’ intention to use Work-unitsForecasting Application (Aplikasi Forecasting Satker – AFS) are perceived usefulness, perceivedease of use, attitude, external influence, interpersonal influence, subjective norm, facilitating, andself efficacy.